Transient cerebral ischaemic attacks–management and prognosis. Issue 667 (May 1981) - Roden, S.; Low-Beer, T.; Carmalt, M.; Cockel, R.; Green, I.
Abstract : Fifty patients who had recently had a transient ischaemic attack took part in a double-blind cross-over trial of sulphinpyrazone 200 mg 4 times daily against placebo. Each treatment was given for 4 months. The incidence of recurrences was much greater in the initial 4 months but there was no difference between the 2 treatments. A follow-up of 39 of the patients showed that 2 years later 90% of those who had not had a recurrence during the 8 months had suffered no further neurological events whereas of those who did have a recurrence during the study only 47% had no further neurological events.